Good Governance and Institutional Reforms : Catalysts for Trade Growth in Singapore - Burkova, Mariia; Shymanska, Kateryna; Mammadov, Orkhan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis "Good Governance and Institutional Reforms: Catalysts for Trade Growth in Singapore" explores how institutional reforms have shaped Singapore’s trade performance and economic growth over time. Using both qualitative analysis and regression models, it examines which institutions played a central role, and how principles like transparency and accountability contributed to long-term trade stability. The study finds that institutional quality, especially in digital customs systems and legal enforcement, strongly correlates with increased trade volume and foreign direct investment. The Singaporean model, while not directly transferable, offers insights that may be adapted by other small, open economies.
Vedoucí práce: Kateryna Shymanska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses